SPINAL CORD COMPRESSION BY METASTATIC THORACIC SPINE PARAGANGLIOMA - Khan, Noman Ahmed Jang; Ullah, Saad; Siddiqui, Hafiz Umair; Karim, Arsalan (Journal of Ayub Medical College Abbottabad, 2016)
Paragangliomas are rare neuroendocrine tumours most commonly located in the adrenal glands. The overall incidence of paragangliomas is 0.8 per 100,000 persons, but the incidence of malignant paraganglioma was found to be 93 cases out of 400 million persons in United States. We present a case of 50 year old male who came to the hospital with back pain and progressive bilateral lower limb weakness for the past 6 months. Imaging studies revealed enhancing lesions on dorsal spines. Bone scintigraphy showed increased tracer uptake at multiple sites. Bone biopsy and immune-histochemical staining proved metastatic paraganglioma. After a thorough literature search only few cases of metastatic spine paraganglioma causing spinal cord compression have been reported to date. Keywords: Paraganglioma; spinal cord compression